The rice enhancer of zeste [E(z)] genes SDG711 and SDG718 are respectively involved in long day and short day signaling to mediate the accurate photoperiod control of flowering time - Liu, Xiaoyun; Zhou, Chao; Zhao, Yu; Zhou, Shaoli; Wang, Wentao; Zhou, Dao-Xiu (Frontiers in Plant Science, 2014)
Recent advances in rice flowering studies have shown that the accurate control of flowering by photoperiod is regulated by key mechanisms that involve the regulation of flowering genes including Heading date1 (Hd1), Early hd1 (Ehd1), Hd3a, and RFT1. The chromatin mechanism involved in the regulation of rice flowering genes is presently not well known. Here we show that the rice enhancer of zeste [E(z)] genes SDG711 and SDG718, which encode the polycomb repressive complex2 (PRC2) key subunit that is required for trimethylation of histone H3 lysine 27 (H3K27me3), are respectively, involved in long day (LD) and short day (SD) regulation of key flowering genes. The expression of SDG711 and SDG718 is induced by LD and SD, respectively. Over-expression and down-regulation of SDG711 respectively, repressed and promoted flowering in LD, but had no effect in SD. By contrast, down-regulation of SDG718 had no effect in LD but delayed flowering in SD. SDG711 and SDG718 repressed OsLF (a repressor of Hd1) respectively in LD and SD, leading to a higher expression of Hd1 thus late flowering in LD and early flowering in SD. SDG711 was also found to be involved in the repression of Ehd1 in LD. SDG711 was shown to directly target to OsLF and Ehd1 loci to mediate H3K27me3 and gene repression. The function of the rice E(z) genes in LD repression and SD promotion of flowering suggests that PRC2-mediated epigenetic repression of gene expression is involved in the accurate photoperiod control of rice flowering.